2006
DOI: 10.1111/j.1464-5491.2006.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase gene is associated with diabetic macroangiopathy in Japanese Type 2 diabetic patients

Abstract: Aims The aldose reductase (AR) gene, a rate-limiting enzyme of the polyol pathway, has been investigated as a candidate gene in determining susceptibility to diabetic microangiopathy. However, the association of the AR gene with diabetic macroangiopathy has not been investigated. Therefore, the present study was conducted to determine whether genetic variations of AR may determine susceptibility to diabetic macroangiopathy.Methods There were 378 Type 2 diabetic patients enrolled in this study. A single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…All of their observations were improved by an AR inhibitor. The aforementioned previous studies, and the novel findings of Tang et al . and Vedantham et al .…”
Section: Pathogenesis Of Ischemic Cerebrovascular Disorders In Diabetesmentioning
confidence: 72%
See 1 more Smart Citation
“…All of their observations were improved by an AR inhibitor. The aforementioned previous studies, and the novel findings of Tang et al . and Vedantham et al .…”
Section: Pathogenesis Of Ischemic Cerebrovascular Disorders In Diabetesmentioning
confidence: 72%
“…Previous studies by our group and others have suggested that hyperglycemia‐induced polyol pathway hyperactivity might, in part, play an important role in the development of diabetes atherosclerosis. Recently, Tang et al .…”
Section: Pathogenesis Of Ischemic Cerebrovascular Disorders In Diabetesmentioning
confidence: 83%
“…In Japanese type 2 diabetic patients, genetic polymorphism of AR has been associated with diabetic macroangiopathy. Clearly, larger studies are warranted to establish the association between AR gene polymorphism and diabetic cardiovascular disease 60.…”
Section: Polymorphisms Of Ald2 and Risk Of Diabetic Complicationmentioning
confidence: 99%
“…However, it has also been reported that the C-106T polymorphism may contribute to an early development of neurophysiologic deterioration in DM2 patients (Sivenius et al, 2004b). In Japanese DM2 patients, the C-106T variant was also associated with diabetic macroangiopathy, were the CT or TT genotype showed association with increased risk of stroke (Watarai et al, 2006).…”
Section: Aldose Reductasementioning
confidence: 99%